The economic impact of postponing the Olympic Games - Jastrzabek, J. (Summer Olympic Games Tokyo 2020 facing the Coronavirus COVID-19 pandemic, 2021)
The Olympic Games' organization is perceived as an instrument of realization of multiple economic goals, both on the local and national scale. The number and complexity of investments made during the Olympic preparation process is aimed at causing a positive and durable effect in various economic sectors and financial spheres. The selection of Tokyo to host the 2020 Olympic Games also involved a significant impact on the Japanese economy, which has been struggling with stagnation and the accompanying periods of deflation or very low inflation since the 1990s. However, a few months ago, no-one expected that rather than being an economic catalyst, the Games could become a serious problem for the host country, International Olympic Committee (IOC), and Olympic stakeholders. The major reason for this situation is the unprecedented decision for the Games' postponement to 2021 due to the coronavirus (SARS-CoV-2) pandemic. Therefore, the main aim of this chapter is to identify the economic consequences of the postponement of the XXXII Summer Olympic Games Tokyo 2020 in the face of the health and socioeconomic crisis caused by the coronavirus pandemic. The chapter is based on a critical literature review, Tokyo 2020 Candidature File, publications, reports, statistical analysis, and press and media coverage. The analysis proves, among other items, that with the Games' postponement, there is a significant increase in the costs of the Olympic Games' organization and the uncertainty among entrepreneurs and corporations involved in the Olympic preparations and delivery.